EFIKASI DAN KEAMANAN HERBISIDA CAMPURAN ATRAZIN, TOPRAMEZON, DAN NIKOSULFURON DALAM MENINGKATKAN HASIL JAGUNG - Rahma Harti, Adi Oksifa; Dwi Syahrina, Sabrina; Dani, Umar (Papanda Publisher, 2025)
Weed infestation in maize fields can reduce crop growth and yield due to competition for light, water, and nutrients. The use of herbicide mixtures is considered an effective strategy to improve weed control efficacy while minimizing the risk of weed resistance. This study aimed to evaluate the efficacy and crop safety of a herbicide mixture containing atrazine 200 g/l, topramezone 10 g/l, and nicosulfuron 15 g/l on weed control, growth, and yield of maize (Zea mays L.). The research was conducted in Majalengka Kulon Village, Majalengka Regency, West Java, using a non-factorial randomized block design with six treatments and four replications. Treatments consisted of herbicide doses of 1.50, 2.00, 2.50, and 3.00 l/ha, manual weeding, and an untreated control. Observed variables included weed composition and dry weight, phytotoxicity levels, growth parameters, and yield components of maize. The results indicated that the herbicide mixture effectively suppressed dominant weed populations without causing phytotoxic effects on maize plants. The application rate of 2.50 l/ha resulted in the most favorable balance between weed control efficacy and crop safety, suggesting its potential to optimize maize productivity.